Synthesis, structure and properties of 7-((4-amino-5-thio-1,2,4-triazole-3-yl)methyl)-theophylline derivatives - A. S. Hotsulia; Ye. H. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The combination of derivatives of 1,2,4-triazole and theophylline creates fertile soil for biologically active substances. The use of these heterocyclic systems allows the use of simple chemical modification methods and available reagents. This determines the relevance of the chosen direction of scientific research.